Patterns in spatial proximity between venture capital investors and investees in Germany: an empirical analysis - Marko Bender; Eva Lutz (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
The paper analyzes patterns in spatial proximity between venture capital investors and investees. We use a data set of 950 dyads of venture capitalists and German new ventures which have closed a financing round between January 2002 and March 2007. We are the first study to use minimum travel time via car or plane as realistic measure of spatial proximity. Our results indicate that different factors relating to characteristics of the new venture, the venture capitalist and the financing round help explain variations in spatial proximity. We find that spatial proximity is more likely for younger ventures, ventures in knowledge-intensive industries, smaller, less specialized, more experienced, semi-profit oriented, or lead-venture capital investors, as well as for very small or very large investment volumes. Another key finding is that spatial proximity is more likely for consecutive financing rounds. Furthermore, we find the effects to be more pronounced for lead-investors.
Keywords: G24; G31; M13; 330; venture capital; new venture; spatial proximity; entrepreneurial